1997
DOI: 10.1006/viro.1997.8762
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Rotavirus Gene 6 from Different Species by Sequence Analysis and Localization of Subgroup-Specific Epitopes Using Site-Directed Mutagenesis

Abstract: The nucleotide sequence of gene 6 encoding the rotavirus major capsid protein VP6 of EDIM strain (EW) was determined and compared to that of 20 previously reported strains with known subgroup specificities. Multiple alignments of amino acid sequences exhibited a high level of sequence conservation (87 to 99.2%). Site-specific mutagenesis experiments were undertaken to localize regions involved in subgroup specificity. Amino acid positions 305, 315, and a region 296-299 (or 301 for equine strain H-2) were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
1
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 31 publications
4
72
1
1
Order By: Relevance
“…In contrast, all human rotavirus strains phylogenetically related to rotavirus strains of subgroup II specificity have been grouped together in the NSP4-B genotype. It was demonstrated that even closely related VP6 sequences of porcine rotavirus strains could be of different subgroups (Tang et al, 1997). Thus, we cannot speculate on the subgroup specificity of our porcine rotavirus strains based only on phylogenetic analysis of the VP6 fragment.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In contrast, all human rotavirus strains phylogenetically related to rotavirus strains of subgroup II specificity have been grouped together in the NSP4-B genotype. It was demonstrated that even closely related VP6 sequences of porcine rotavirus strains could be of different subgroups (Tang et al, 1997). Thus, we cannot speculate on the subgroup specificity of our porcine rotavirus strains based only on phylogenetic analysis of the VP6 fragment.…”
Section: Discussionmentioning
confidence: 91%
“…The amino acid identity of these two strains with other strains of NSP4-B genotype was less than 90 % (data not shown). Human and animal strains were also analysed in a region spanning aa 241-367 (nt 747-1126 of the VP6 gene) implicated in subgroup specificity (Tang et al, 1997). As shown in the phylogenetic tree of VP6 (Fig.…”
Section: Molecular and Phylogenetic Analysis Of Human Porcine And Bomentioning
confidence: 99%
“…The SG specificities are determined by amino acids located at positions 305, the region between amino acids positions 296 and 299 (SGI) and amino acid position 315 (SGII) (López et al 1994, Tang et al 1997. Many epidemiological studies have used subgrouping enzyme immunoassays (EIAs).…”
mentioning
confidence: 99%
“…Many epidemiological studies have used subgrouping enzyme immunoassays (EIAs). Based upon these analyses, most human isolates fall into SGII (Arista et al 1990, Gómara et al 2001, while most animal isolates fall into SGI (Tang et al 1997). …”
mentioning
confidence: 99%
“…In the case of SG II, the mutation of two contiguous amino acids (Ala305 Asn306 to Asn305 Ala306) in the VP6 protein of porcine rotavirus YM (SG I) enables the protein to be recognized efficiently by the SG II MAb 631/9, while losing its capacity to interact with SG I MAb 255/60. Furthermore, it has been proposed that an Ala residue at positions 172 and 305 contribute to determining reactivity to SG I MAb (MAb 255/60), whereas a Glu residue at position 315 contributes to reactivity to SG II MAb (MAb 631/9) [Tang et al, 1997]. Analysis of the VP6 protein, which encompasses the amino acid positions in the regions implicated in the recognition by SG-specific MAbs, revealed that deduced amino acid sequences of human rotavirus strains determined serologically as SG II, SG (I þ II), or SG non-(I þ II) are indistinguishable from each other [Iturriza-Gomara et al, 2002].…”
Section: Introductionmentioning
confidence: 99%